Analysis of Work System and Maintenance of Solar Power Plant With A Capacity of 10.8 Kwp In Graha YPK PLN - Pawenary Pawenary; Arditiyan Elyas Pradana (Journal Research of Social Science, Economics, and Management, 2023)
As the demand for electricity increases, so does the demand for fossil fuels for power generation, leading to a reduction in the current reserves of fossil fuels, which are also becoming more expensive. By utilizing renewable energy sources, one of which is solar energy, it can be used as an alternative energy source that is environmentally friendly. A grid-connected rooftop solar power plant can reduce the amount of your monthly electricity bill, thereby increasing efficiency. Based on the author's findings on the rooftop PLTS at Graha YPK PLN with a capacity of 10.8 kWp using solar panels with a capacity of 450 Wp as many as 24 panels and one inverter of 15.330 W, there are two factors that cause the results of the energy produced by PLTS to be inconsistent, the first is internal factors for example from solar modules, inverters, and distribution panels. The second is external factors, namely weather, shading and Ambient Air Temperature. The results of the maintenance that has been carried out can be concluded that the maintenance carried out is successful. so that the maintenance activities carried out can be carried out again in the next maintenance. For this reason, this maintenance activity is able to help reduce or overcome problems on the panel such as the panel not working effectively due to the presence of dust attached and even stubborn dirt and so on that cannot be washed away by rainwater